Mutation of TWNK Gene Is One of the Reasons of Runting and Stunting Syndrome Characterized by mtDNA Depletion in Sex-Linked Dwarf Chicken - Hu, Bowen; Yang, Minmin; Liao, Zhiying; Wei, Haohui; Zhao, Changbin; Li, Dajian; Hu, Shuang; Jiang, Xinsheng; Shi, Meiqing; Luo, Qingbin; Zhang, Dexiang; Nie, Qinghua; et al. (Frontiers in Cell and Developmental Biology, 2020)
Runting and Stunting Syndrome (RSS), which is characterized by low body weight, generally occurs early in life and leads to considerable economic losses in the commercial broiler industry. Our previous study has suggested that RSS is associated with mitochondria dysfunction in sex-linked dwarf (SLD) chickens. However, the molecular mechanism of the RSS remains unknown. Based on the molecular diagnostics of mitochondrial diseases, we identified a recessive mutation c. 409G>A (p. Ala137Thr) of Twinkle mitochondrial DNA helicase (TWNK) gene and mitochondrial DNA (mtDNA) depletion in RSS chickens’ livers from strain N301. Bioinformatics investigations supported the pathogenicity of the TWNK mutation that is located on the linker region of Twinkle primase domain and might further lead to mtDNA depletion in chicken. Furthermore, overexpression of the TWNK wild-type increases mtDNA content, whereas overexpression of the TWNK A137T causes mtDNA depletion in vitro. Additionally, the TWNK c. 409G>A mutation showed significant associations with body weight, daily gain, pectoralis weight, crureus weight and abdominal fat weight. Taken together, we corroborated that the recessive TWNK c. 409G>A (p. Ala137Thr) mutation is associated with RSS characterized by mtDNA depletion in SLD chicken.